69th Maverick Rodeo : July 4, 1992 (Cimarron, New Mexico Cimarron Legend, 1992)
Article in the Cimarron Legend on the 60th Maverick Rodeo program.
Master List item # 26
File location is in the Raton File Cabinet
Keywords: Wilson, Edker; Morse, Buddy; Morse, Bebe; Serazio, Bill; Walters, Keith; Coppedge, Barney; G-H Ranch; Kit Carson Inn; C.M. Buenger; Sam Minor Construction; Russell's One Stop; St. James Hotel; Cimarron Stop and Save; Chase Ranch; Northern New Mexico Gas Company; CS Ranch; Zimmer Ranch; Cimarron West; Pacific Stud; U.S. Outfitters; Philmont Scout Ranch; Schwede's Saloon; Jeffers Livestock Company; Local History; Rodeo; Roping; Bareback Bronc Riding; Team Roping; Sinior Barrel Race; Wild Cow Milking; Pole Bending; Calf roping; Saddle bronc riding; Horse race; Bull riding; Cimarron, New Mexico